A scanning electron microscopy investigation of semiconductor metal chalcogenide thin films: A review - Ho, Soon Min (Scholars Research Library, 2016)
Nowadays, scanning electron microscopy is a valuable tool that could be applied in a number of applications including forensic sciences, metallurgy and nanotechnologies. In view of researchers, it provides a better overall visual image of the sample and makes the quick resolution of tough analytical problems effectively. In this work, the characterization of thin films prepared under various deposition conditions by using scanning electron microscopy was discussed and reported.